2014
DOI: 10.1002/2013jd021186
|View full text |Cite
|
Sign up to set email alerts
|

Radiative forcing of organic aerosol in the atmosphere and on snow: Effects of SOA and brown carbon

Abstract: Organic aerosols (OA) play an important role in climate change. However, very few calculations of global OA radiative forcing include secondary organic aerosol (SOA) or the light-absorbing part of OA (brown carbon). Here we use a global model to assess the radiative forcing associated with the change in primary organic aerosol (POA) and SOA between present-day and preindustrial conditions in both the atmosphere and the land snow/sea ice. Anthropogenic emissions are shown to substantially influence the SOA form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
252
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(276 citation statements)
references
References 122 publications
(205 reference statements)
19
252
5
Order By: Relevance
“…The estimated OC forcing has a fourfold increase from 0.2 W m −2 (for a mean OC concentration of 13.8 ng g −1 during to 0.84 W m −2 (for a mean OC concentration of 61.3 ng g −1 in 2006), which are 27 and 43 % of the corresponding BC-in-snow forcing, respectively. The OC / BC forcing ratios based on our simple guesses are larger than the upper bound of the estimates (i.e., 24 %) by Lin et al (2014).…”
Section: Radiative Forcing Induced By Carbonaceous Aerosols In Tibetacontrasting
confidence: 52%
See 1 more Smart Citation
“…The estimated OC forcing has a fourfold increase from 0.2 W m −2 (for a mean OC concentration of 13.8 ng g −1 during to 0.84 W m −2 (for a mean OC concentration of 61.3 ng g −1 in 2006), which are 27 and 43 % of the corresponding BC-in-snow forcing, respectively. The OC / BC forcing ratios based on our simple guesses are larger than the upper bound of the estimates (i.e., 24 %) by Lin et al (2014).…”
Section: Radiative Forcing Induced By Carbonaceous Aerosols In Tibetacontrasting
confidence: 52%
“…A more recent observational study by Dang and Hegg (2014) quantified the light absorption by different light-absorbing particulates in snow, and suggested that humic-like substances and polar OC contributed 9 and 4 % to the total light absorption, respectively. Despite the substantial uncertainties in brown carbon optical properties, a recent global modeling study (Lin et al, 2014), in which a range of optical properties of brown carbon taken from the literature were applied to OC-in-snow concentrations simulated in a global chemical transport model, showed that the global OC forcing in land snow and sea ice is up to 24 % of that caused by BC. Thus, the contribution of OC in snow to the surface albedo reduction is likely to be important, which has also been considered in recent climate modeling studies (Qian et al, 2015).…”
Section: Radiative Forcing Induced By Carbonaceous Aerosols In Tibetamentioning
confidence: 99%
“…In western North America, Dang and Hegg (2014) suggested that OC was responsible for more than 10 % of the total light absorption. A global model by Lin et al (2014) estimated the role of OC in the reduction of snow albedo and suggested that the radiative forcing (RF, the difference between insolation (sunlight) absorbed by the snow surface and energy radiated back to space in this study) of OC deposited to land snow and sea ice ranges from +0.0011 to +0.0031 W m −2 , contributing as much as 24 % of the forcing caused by BC in snow and ice. The RF of snow pit dissolved organic carbon (DOC) from a Tibetan glacier was calculated to be 0.43 W m −2 , indicating that DOC in snow needed to be taken into consideration for the accelerating glacial melt on the TP .…”
mentioning
confidence: 74%
“…Due to its light-absorbing properties (Andreae and Gelencsér, 2006;Bahaur et al, 2012;Yan et al, 2016), OC in snow cover can also absorb solar radiation and reduce the surface albedo. Previous studies indicated that OC was responsible for more than 10-40 % of the light absorption Doherty et al, 2010;Lin et al, 2014;Wang et al, 2015). Not considering OC in snow will underestimate the LAP impact on albedo reduction and RF, and this should not be ignored in the future.…”
Section: Limitations and Implications For Snow Cover And Glaciers On mentioning
confidence: 99%
“…Open biomass burning (BB) is one of the largest global sources of BC and organic carbon (OC), and biomass burning emissions have a significant direct effect on the Earth's radiative balance (Bond et al, 2013). When biomass burning emissions interact with clouds, there are significant semi-direct and indirect effects, and the magnitude of the semi-direct effects depends on the optical properties of the emitted aerosols (Sakaeda et al, 2011;Lin et al, 2014;Jacobson, 2014).…”
mentioning
confidence: 99%